Vehicle classification using an array of low-cost web cameras - Tan, Jia Jin. (2013)
Vehicle classification has been an important topic that is being widely discussed because of its useful applications, one of it is that can ease the public road user in terms of providing smoother road traffic with the help of congestion traffic control system. This system is usually encompasses with high cost camera that make it even more expensive and is not portable. However, with the speedy advancement of computer vision